- Luthertolkningen i 1812-krøniken - Holm, Anders (Grundtvig-studier, 2013)
Luthertolkningen i 1812-krøniken[The Interpretation of Luther in Grundtvig’s World Chronicle of 1812]By Anders Holm Grundtvig grew up in two Lutheran vicarages. Both homes were characterized by Lutheran orthodoxy but could not ignore the critical thoughts of the Enlightenment. During his studies at the University of Copenhagen Grundtvig was convinced of the truth of the new philosophy of reason. His father’s wish in 1810, however, that he become his curate demanded that he reconsidered the world-view which he thought to have left behind. It all ended in a crisis and a nervous breakdown, which resulted in his return to a faith strongly inspired by Luther.Grundtvig’s book Brief View of the World Chronicle in Context, 1812, aimed to find God in the course of events of world history. His method was to describe and evaluate the past and the present with the Bible as the standard, and he chose to concentrate on Luther and Melanchthon as the principal characters of the Reformation. Luther dismissed everything that was not based upon clear words from scripture as lies and delusions; Melanchthon was a skilful interpreter of Luther’s radical statements, expressing himself distinctly and unequivocally. After the deathof Luther, however, Melanchthon was influenced by Reformed theology. The principal difference between Reformed and Lutheran cultures, Grundtvig claimed, sprung from the fact that Zwingli had emphasized reason whereas Luther wasmore poetically inclined. Accordingly, two cultures with diverging directions developed. The belief in reason and inborn abilities had led the followers of the Reformed Church to social uprising, and their mentality made them oppose people of other opinions. Lutheran believers and supporters on the other hand, Grundtvig conceived of as more obedient to authority. In contrast to the Reformed culture, the Lutherans appreciated elements of beauty in their churches such as art, music and hymn singing.Finally, the assessment of the young Grundtvig as a Lutheran orthodox is discussed, with the result that this view cannot be confirmed. Grundtvig does not show any tendency towards building coherent dogmatics from single biblicalpassages. But the Bible still has a role to play in the judging of the past because, as a whole, it points to the true Christianity in history.